FAKTOR PENENTU KINERJA PERBANKAN DI DALAM PERUBAHAN KEUANGAN DI INDONESIA - Achmad Syarifuddin; Letty Prisma Resmi (Universitas 17 Agustus 1945 Jakarta, 2018)
This research used the second data within banking syariah, where the data banking is a banking syariah listed in the Indonesian Banking during period 6 years ago. The type of datain this study is the method of data analysis used is Multiple Regression. The test results showed the influence negative hypothesis between the Credit Risk toward banking performance syariah listed on the Indonesian Banking. The influence negative hypothesis between the Liquidity Risk toward banking performance syariah listed on the Indonesian Banking. The influence negative hypothesis between the Capital Risk toward banking performance syariah listed on the Indonesian Banking. The influence negative hypothesis between the Operational Risk toward banking performance syariah listed on the Indonesian Banking. The implication of this study is to Islamic banking management uses this information as a benchmark study to enhance the performance of banks and customers for consideration whether to save and depositing the funds in the bank.